Neonatal anesthesia in a country in sub-Saharan Africa. - PDG Mawandza; GF Otiobanda; G Ekouya Bowassa; Departement of pediatric, Faculty of sciences health, University Marien Ngouabi, Brazzaville Congo; C Mboutol-Mandavo; JA Mbongo (Pediatric Anesthesia and Critical Care Journal, 2019)
Introduction The newborn is a particular ground for the anesthetist. In Africa, anesthesia for neonatal surgery is performed un- der precarious conditions. The aim is to study the practice of anesthesia in neonatal surgery in a francophone coun- try of sub-Saharan Africa. Materials and methods This is 4-year retrospective descriptive study from Janu- ary 2014 to December 2017 at Brazzaville University Hospital. All patients anesthetized for neonatal surgery aged from 0 to 28 days were included. Results The frequency of this surgery was 2.3%. The average age was 9.26 days (1 and 25 days). The average weight was 2672g (1580 and 4000g). Bowel obstruction (66%) and peritonitis (14%) were the most common diagnoses. Pa- tients were ASA1, ASA2 and ASA3 in 45.8%, 39.6% and 14.6%, respectively. Anesthesia was general in all cases with intravenous induction in 84% and with halogenesis in 16%. Propofol and ketamine were used in 56% and 26%. Transfusion was performed in 34%. Intraoperative incidents and complications (46.8%) were dominated by respiratory ones: bronchospasm 13.6%, hypoxia 4.5%, difficult intubation 18.2% and haemodynamic ones: tach- ycardia 27.3% and bradycardia 36, 4%. An anesthesiolo- gist doctor was present in the operating room in 90%. Mortality rate was 22%. Conclusion Despite the difficult conditions of exercise in anesthesia, practices are relatively reliable, but mortality rate can be reduced by targeted training and the improvement of working environment.